Effect of Dietary Vitamin E on the Production of Platelet 12-Hydroxyeicosatetraenoic Acid (12-HETE) - Pritchard, K A; Greco, N J; Panganamala, R V (Thrombosis and Haemostasis, 1986)
Collagen and thrombin challenged platelets from vitamin E-deficient rabbits generated significantly more 12-HETE when compared to the platelets from vitamin E-supplemented rabbits. Similarly, conversion of arachidonic acid to 12-HETE was increased in platelets from vitamin E-deficient rabbits. These data show that vitamin E plays a role not only in deacylation of platelet phospholipids but also in the lipoxygenase mediated reactions.
Keywords: Rabbit; Platelets; Vitamin E; 12-HETE